Implementasi Konsep Subject Matter Pada Interior Rumah Duka di Surabaya - Livia Wijaya; Ronald Hasudungan Irianto Sitindjak; Hendy Mulyono (Intra, 2019)
All this time, funeral home facilities that have been operating for a long time in Surabaya mostly focuses on the functional aspects. Orientation tends to only accommodate activities but less on understanding the human subject concerned. Funeral Home Interior Design is part of the act of caring for a death event. The point of design will focus on the subject especially for the mourners who are in griev. In order to help them relief both on physical and psychological aspects. Through Funeral Home Design, the meaning and essence of the end of life can be conveyed to those who visit and delivered the deceased. So that might open a new positive thoughts and notions on a death event. This is also a representation of hospitality that aim to improve the quality of a death service.